Pengaruh Current Ratio, Debt to Equity Ratio dan Firm Size terhadap Return on Equity pada PT.Adhi Karya (PERSERO) Periode 2015-2021 - adinda, vira; Rindi Mesya, Damayanti (Universitas Bojonegoro, 2023)
This study examines the impact of the Current Ratio (CR), Debt to Equity Ratio (DER), and Firm Size on Return on Equity (ROE) at PT. Adhi Karya from 2015 to 2021. The data were obtained from the company's publicly available financial reports during this period. This research employs a quantitative descriptive approach. The findings reveal that the Current Ratio (CR) does not have a partial effect on ROE, while the Debt to Equity Ratio (DER) and Firm Size significantly influence ROE. Additionally, CR, DER, and Firm Size collectively affect ROE. The Coefficient of Determination (R2) indicates that these variables account for 64% of the variation in ROE, with the remaining 36% influenced by other factors not explored in this study.